Profile of consumers of caranguejo-uça" of the Municipality of Capanema in northeastern Pará (Research, Society and Development, 2020)
This study aimed to analyze the profile of consumers of caranguejo-uça", in the village of Belton, northeastern Pará. The study was developed using questionnaires with objective questions, applied in the period from January to February 2019. The amount of people who answered the questionnaire amounted to 141. The consumer market of crab in the municipality of Capanema, had as its main requirement at the time of purchase, the price factors and hygiene of the product. As a conclusion to this research brought to light the main problems faced by consumers when it comes to hygiene issue, given that the structure where the product is exposed is precarious, requiring minimum metrics such as water, proper storage location and where to dispose of the crabs dead. When the price on sale of crab is above the expected to demand, consumers tend to replace by fish.